2020
DOI: 10.1016/j.csbj.2019.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between Hippo and Wnt signalling pathways in intestinal crypts: Insights from an agent-based model

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Discrete cell-based models-independent of being on-or off-lattice-can be coupled to PDE models for simulating the concentration of chemical compounds in the cellular environment or even an ODE model for simulating intracellular dynamics (Cilfone et al 2015;Macklin et al 2016;Ward et al 2020). An extensive review of cell-based models for general tissue mechanics can be found in Van Liedekerke et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Discrete cell-based models-independent of being on-or off-lattice-can be coupled to PDE models for simulating the concentration of chemical compounds in the cellular environment or even an ODE model for simulating intracellular dynamics (Cilfone et al 2015;Macklin et al 2016;Ward et al 2020). An extensive review of cell-based models for general tissue mechanics can be found in Van Liedekerke et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive list of published simulation studies that deal with or include the Wnt signaling pathway is found in Table 1 . Out of the 31 simulation studies ([ 28 58 ]), which we have found, we have chosen to collect provenance information from 19 studies, shown in bold in Table 1 . Some of these Wnt models have already been discussed in previous reviews [ 23 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hippo and Wnt signaling are closely linked to each other[ 63 ]. YAP1 increases the transcriptional activity of β-catenin, while active Hippo signaling leads to the formation of the destruction complex of Wnt signaling[ 64 , 65 ].…”
Section: The Complex Regulation Network Of Wnt Signalingmentioning
confidence: 99%